Smart City in Indonesia: Review Studies and Lessons for Sumatra - Gunawan, Raihan (Business and Sustainability, 2022)
Smart city is a concept that has gained increasing attention in Indonesia in recent years. This study uses bibliometric analysis to explore the development and trends of smart city research in Indonesia from 469 articles. The results show that the number of publications on smart city in Indonesia has increased significantly in recent years. Employing various bibliometric techniques, the study's results reveal key insights into the dynamics of Smart City research in Indonesia. The most prominent keywords reflect the multidisciplinary nature of the topic and its relevance to urban development, technology, governance, and environmental concerns. This study also found that in Sumatra, the development of Smart Cities is still in its early stages, but has the potential to improve the quality of life for citizens and address urban challenges. By comprehensively mapping the intellectual landscape of Smart City research in Indonesia, this research contributes to a better understanding of the key themes, trends, and collaborative networks shaping the discourse in this important domain.